2022
DOI: 10.1038/s41586-022-05448-9
|View full text |Cite|
|
Sign up to set email alerts
|

Common and rare variant associations with clonal haematopoiesis phenotypes

Abstract: Clonal haematopoiesis involves the expansion of certain blood cell lineages and has been associated with ageing and adverse health outcomes 1 – 5 . Here we use exome sequence data on 628,388 individuals to identify 40,208 carriers of clonal haematopoiesis of indeterminate potential (CHIP). Using genome-wide and exome-wide association analyses, we identify 24 loci (21 of which are novel) where germline genetic variation influences predisposition to CHIP, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
136
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 64 publications
13
136
1
Order By: Relevance
“…The X chromosome, particularly the inactive X, is more frequently mutated in cancer genomes 19 and is late replicating relative to autosomes, potentially increasing susceptibility to chromosomal alterations 20 . While few genome-wide association studies (GWAS) of mLOX have been reported to date 14,21 , GWAS of mosaic loss of the Y chromosome (mLOY) in men has identified hundreds of susceptibility loci 11-13,22 , many of which highlight genes involved in cell cycle regulation and cancer susceptibility. Here we describe insights from epidemiologic and genetic analyses of X chromosome loss from a combined meta-analysis of 904,524 women.…”
Section: Introductionmentioning
confidence: 99%
“…The X chromosome, particularly the inactive X, is more frequently mutated in cancer genomes 19 and is late replicating relative to autosomes, potentially increasing susceptibility to chromosomal alterations 20 . While few genome-wide association studies (GWAS) of mLOX have been reported to date 14,21 , GWAS of mosaic loss of the Y chromosome (mLOY) in men has identified hundreds of susceptibility loci 11-13,22 , many of which highlight genes involved in cell cycle regulation and cancer susceptibility. Here we describe insights from epidemiologic and genetic analyses of X chromosome loss from a combined meta-analysis of 904,524 women.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 | CH is associated with health outcomes across many organ systems.Boxes shaded green highlight associations between CH and diseases that were replicated by Kessler et al9 . COPD, chronic obstructive pulmonary disease.…”
mentioning
confidence: 76%
“…The most common being loss of Y or X chromosomes, otherwise known as mosaic loss of Y and X (mLOY and mLOX, respectively). Similar to the gene-specific analyses, the authors Boxes shaded green highlight associations between CH and diseases that were replicated by Kessler et al 9 . COPD, chronic obstructive pulmonary disease.…”
mentioning
confidence: 81%
See 2 more Smart Citations